Effects of acute and chronic psychological stress on platelet aggregation in mice. (March 2014) - Matsuhisa, Fumikazu; Kitamura, Nobuo; Satoh, Eiki
Abstract Although psychological stress has long been known to alter cardiovascular function, there have been few studies on the effect of psychological stress on platelets, which play a pivotal role in cardiovascular disease. In the present study, we investigated the effects of acute and chronic psychological stress on the aggregation of platelets and platelet cytosolic free calcium concentration ([Ca2+]i). Mice were subjected to both transportation stress (exposure to novel environment, psychological stress) and restraint stress (psychological stress) for 2 h (acute stress) or 3 weeks (2 h/day) (chronic stress). In addition, adrenalectomized mice were subjected to similar chronic stress (both transportation and restraint stress for 3 weeks). The aggregation of platelets from mice and [Ca2+]i was determined by light transmission assay and fura-2 fluorescence assay, respectively. Although acute stress had no effect on agonist-induced platelet aggregation, chronic stress enhanced the ability of the platelet agonists thrombin and ADP to stimulate platelet aggregation. However, chronic stress failed to enhance agonist-induced increase in [Ca2+]i. Adrenalectomy blocked chronic stress-induced enhancement of platelet aggregation. These results suggest that chronic, but not acute, psychological stress enhances agonist-stimulated platelet aggregation independently of [Ca2+]i increase, and the enhancement may be mediated by stress hormones secreted from the adrenal glands.